The use of music in nursing care for psychological distress reduction in cancer patients: A scoping review protocol - Karena Cristina da Silva Leal; Maria Améllia Lopes Cabral; Myrza Torres Ferreira; Danielle de Oliveira Rocha; Lara Dantas de Rubim Costa; Geovana Caroliny de Morais Silva; Louise Constância de Melo Alves Silva; Daniele Vieira Dantas; Rodrigo Assis Neves Dantas (PLoS ONE, 2025)
Psychological distress in cancer patients is a frequent and complex condition that significantly compromises quality of life, from diagnosis to palliative care. In this context, the use of music emerges as a promising, safe, and low-cost complementary practice capable of alleviating symptoms such as emotional distress. However, there are still gaps in the literature regarding the types, contexts, and specific effects of musical interventions in cancer patients. Thus, this protocol proposes a scoping review to map the available scientific evidence on the use of music as an intervention for the reduction of psychological distress in cancer patients. The methodology will adhere to the guidelines of the Joanna Briggs Institute and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews (PRISMA-ScR) checklist. The search will be conducted across twenty data sources, including PubMed Central, Latin American and Caribbean Literature in Health Sciences, Cumulative Index to Nursing and Allied Health Literature, Web of Science, Scientific Electronic Library Online, Cochrane Library, Elsevier’s Scopus, ScienceDirect, Wiley Online Library, and the Virtual Health Library. For gray literature, Catalog of Theses and Dissertations of the Coordination for the Improvement of Higher Education Personnel, the Networked Digital Library of Theses and Dissertations,Google Scholar, European Thesis Portal; Electronic Thesis Online Service; Open Access Scientific Repository of Portugal; National Theses and Dissertations; Theses Canada; Treasury of the National Library of Australia; Online Academic Archive will be searched. Study screening and selection will be performed independently by two researchers according to the inclusion and exclusion criteria. Relevant data will be extracted into a structured spreadsheet, including study characteristics, type and setting of the musical intervention, outcomes related to psychological distress, and the role of nursing. The findings are expected to inform clinical practice, particularly in the field of oncology nursing, as well as to identify gaps for future research.